2003
DOI: 10.1007/s11883-003-0081-3
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein(a) and the atherothrombotic process: Mechanistic insights and clinical implications

Abstract: Although many epidemiologic studies have pointed at an association between plasma levels of lipoprotein(a) (Lp(a)) and cardiovascular risk, the data obtained have been conflicting because of a number of factors, particularly those dealing with plasma storage, lack of assay standardization, population sample size, age, gender, ethnic variations, and variable disease endpoints. Moreover, the attention has been primarily focused on whole Lp(a), with relatively less emphasis on its constituent apolipoprotein(a) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0
6

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 60 publications
1
32
0
6
Order By: Relevance
“…From the cardiovascular standpoint, various mechanisms have been suggested to explain the athero-thrombogenic potential of Lp(a) and distinct domains in apo(a) have been identified for each reported function (1). Recently, we have shown that apo(a), its C-terminal domain and one of the fragments comprising the KV-PD region stimulated the production and secretion of IL-8 in human THP-1 macrophages grown in culture (5).…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations
“…From the cardiovascular standpoint, various mechanisms have been suggested to explain the athero-thrombogenic potential of Lp(a) and distinct domains in apo(a) have been identified for each reported function (1). Recently, we have shown that apo(a), its C-terminal domain and one of the fragments comprising the KV-PD region stimulated the production and secretion of IL-8 in human THP-1 macrophages grown in culture (5).…”
Section: Figmentioning
confidence: 99%
“…The other kringles, classified from 1 to 10, occur as a single copy each differing in amino acid sequence (1). The function of some of these kringles has been recognized.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Lipoprotein(a) is an atherogenic particle, that is a LDLlike substance which structure is apolipoprotein(a) [Apo(a)] attached with disulfide bond to apolipoprotein B-100 on the LDL core [4]. Apo(a) is synthesized and secreted into the circulation by liver.…”
Section: Introductionmentioning
confidence: 99%
“…Lipoprotein (a) (Lp (a)) has been established as an independent risk factor for CAD. (2) . Therefore, this study was designed to compare the serum Lp (a) level in patients with type 2 diabetes and nondiabetic individuals.…”
Section: Introductionmentioning
confidence: 99%